Predictors of nurses’ caring practice for critically ill patients in critical technological environments: A cross-sectional survey study - Li, Yinglan; Kongsuwan , Waraporn (Belitung Raya Foundation, Indonesia, 2021)
Background: Caring practice for critically ill patients refers to the actions/behaviors/performance of nurses while caring for critically ill adult patients in the intensive care unit (ICU). Although the caring practice is vital in ICUs and complex due to the multitude of availabletechnologies, research on ICU nurses’ caring practice and its predictive factors are lacking. Objective: This study aimed to explore the level of nurses’ caring practice for critically ill patients in critical technological environments in China and its predictors. Methods: This was a cross-sectional online survey study with 218 ICU nurses in 29 tertiary hospitals of Guizhou province, China, from 1st to 30th April 2020. Data were collected by using e-questionnaires made in the Questionnaire Star program, including the Demographic Data Questionnaire (DDQ), Practice of Technological Competency as Caring in Nursing Instrument (P-TCCNI), Influence of Technology Questionnaire (ITQ), and Nurses’ Professional Value Scale (NPVS). The questionnaires were content validated by three experts. Cronbach’s alpha coefficient was 0.96 for the P-TCCNI, 0.70 for the ITQ, and 0.95 for the NPVS. Links to the questionnaires were distributed by research assistants to WeChat groups including target participants. Statistical Package for the Social Science (SPSS) program version 26 (IBM Corporation, Armonk, NY, USA) was used for data analysis. Descriptive and inferential statistics were used to analyze the data. Multiple linear regression analysis using stepwise solution analysis was performed to identify unique predictors of nurses’ caring practice. Results: The level of nurses’ caring practice for critically ill patients was high (mean = 87.30, standard deviation = 13.73). The professional value was a significant predictor of nurses’ caring practice (β = 0.41, p = 0.00). Conclusion: ICU nurses exhibited a high level of caring practice. Professional value was a significant predictor of ICU nurses’ caring practice. Nursing administrators should understand the current situation of caring practice in critical technological environments and design strategies to maintain and improve ICU nurses’ professional value to increase the level of caring practice.